Condition of shrimp culture ponds in the South Coast of Cilacap Regency, Central Java, Indonesia - Utami Ardhana Reswari (EDP Sciences, 2021)
In recent years, aquaculture has begun to develop on the southern coast of Cilacap, which is carried out on sandy land without being surrounded by mangroves and is generally operated with intensive methods. This pool is owned by individuals or companies. This paper aims to descriptively describe aquaculture condition in the area, especially regarding the status, production, and management efforts, based on the results of field observations and literature studies. The area of intensive shrimp cultivation in Cilacap Regency in 2020 is ±227 ha, and the number of cultivators (intensive) is 270 people. The overall value of shrimp production in 2018 in Cilacap Regency was Rp. 52,898,856,945.00, an increase of 38% compared to 2017, which was Rp. 38,446,305.875.00. Adipala Regency has a large pond area, but the production value and production are less than other districts. In the development of ponds, some locations are made quite close to the beach, without a green belt. Seawater is taken directly from the sea by suction using a pump or by drilling. Likewise, freshwater extraction is carried out through drilling into the ground. Wastewater is discharged directly into the sea because there is no Wastewater Treatment Plant (WWTP).